The Forkhead transcription factor UNC-130 is required for the graded spatial expression of the UNC-129 TGF-β guidance factor in C. elegans - Nash, Bruce (Cold Spring Harbor Laboratory Press, 2000)
Secreted proteins required for cellular movements along the circumference of the body wall in Caenorhabditis elegans include UNC-6/netrin and the novel TGF-β UNC-129. Expression of these proteins is graded along the dorsoventral (D/V) axis, providing polarity information to guide migrations. Here we show that the graded expression of UNC-129 in dorsal but not ventral body muscles depends on unc-130, which encodes a Forkhead transcription factor. The phenotype of unc-130 mutants closely mimics the reported effects of ectopically expressing unc-129 in both dorsal and ventral body muscles (Colavita et al. 1998). This fits our present finding that unc-130 cell autonomously represses unc-129 expression in the ventral body muscles. Thus the cell-specific effects of unc-130 on ventral, but not dorsal, body muscle expression of unc-129 accounts for the D/V polarity information required for UNC-129-mediated guidance. Genetic interactions between unc-130 and other guidance genes show that several molecular pathways function in parallel to guide the ventral to dorsal migration of distal tip cells (DTCs) and axonal growth cones in C. elegans. Genetic interactions confirm that UNC-129 does not require the only known type II TGF-β receptor in C. elegans (DAF-4) for its guidance functions. Also, unc-130 is partially required for male tail morphogenesis and for embryogenesis.